Ventricular Arrhythmia Burden in Patients With Heart Failure and Cardiac Resynchronization Devices: The Importance of Renal Function. (6th October 2016) - GANESHA BABU, GIRISH; WEBBER, MATTHEW; PROVIDENCIA, RUI; KUMAR, SANJEEV; GOPALAMURUGAN, AERAKONDAL; ROGERS, DOMINIC P.; DAW, HOLLY LOUISE; AHSAN, SYED; KHAN, FAKHAR; CHOW, ANTHONY; LOWE, MARTIN; ROWLAND, EDWARD; et al.
VA Burden in Patients With HF: Background: Chronic kidney disease (CKD) is a risk factor for arrhythmias in patients with heart failure (HF). However, the effects of CKD on ventricular arrhythmia (VA) burden in patients with cardiac resynchronization therapy and defibrillator (CRT‐D) devices in a primary prevention setting are unknown. Objective: To determine whether baseline CKD is associated with increased risk of VA in patients implanted with primary prevention CRT‐D devices. Methods and Results: In this retrospective study, 199 consecutive primary prevention CRT‐D recipients (2005–2010) were stratified by estimated glomerular filtration rate (eGFR) levels prior to device implantation with 106 (53.2%) ≥CKD III (eGFR < 60 mL/min/1.73 m 2 ) (CKD group). CKD group patients were significantly older (70.0 ± 10 years vs. 61.3 ± 12 years, P < 0.05) with higher prevalence of ischemic cardiomyopathy (56.2% vs. 40.2%, P < 0.05). Detected ventricular tachycardia (VT)/ventricular fibrillation (VF) episodes resulting in device therapy occurred significantly more frequently in the CKD group [40/106(37.8%)] than controls [24/93(25.8%)], (odd ratio [OR] = 1.74, 95% confidence interval [CI] = 1.01–3.2, P = 0.05). At 5‐year follow‐up, interval censored data analysis showed 41% VT/VF incidence in the CKD group compared to 24% incidence in controls (P < 0.05). Cox proportional hazards model identified CKD > III as the only predictor of sustained VA in this group (adjusted hazard ratio [HR] 2.92, CI = 1.39–6.1, P = 0.004). Conclusion: Baseline CKD is a strong independent risk factor for VA in primary prevention CRT‐D recipients. Further understanding of the underlying arrhythmogenic mechanisms relating to CKD may be of interest to allow appropriate correction and prevention. Device programming in this cohort may need to reflect this increased risk.